Asymptotic m-phase soliton-type solutions of a singularly perturbed Korteweg?de Vries equation with variable coefficients - Samoilenko, V. G.; Samoilenko, Yu. I. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We propose an algorithm for the construction of asymptotic m-phase soliton-type solutions of a singularly perturbed Korteweg – de Vries equation with varying coefficients and establish the accuracy with which the main term asymptotically satisfies the considered equation.